2010
DOI: 10.4103/0250-474x.62255
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of indomethacin release from polyethylene glycol tablet fabricated with mold technique

Abstract: The purpose of this study was to use polyethylene glycol as a carrier to improve the solubility of an aqueous insoluble drug by melting and molding method. The release of dissolved drug was designed to be subsequently sustained with an addition of xanthan gum. The release of indomethacin from the developed system into phosphate buffer pH 6.2 was conducted using the dissolution apparatus. This carrier system could effectively enhance the solubility of indomethacin and an addition of xanthan gum could sustain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The chemical instability witnessed with IND/SAC/PEG 6000 cocrystals may be due to the PEG 6000 being soluble with one of the bulk components. Phaechamud et al noted solubilization of IND when using a 7:3 PEG 4000/PEG 400 mixture as an inert drug carrier, and El-Badry and colleagues found that pure PEG 4000 also had a solubilizing effect when interacting with IND. , Given these findings, it is reasonable for one to assume that when left for a period of time, the IND began to solubilize within the PEG 6000 matrix causing the chemical instability noted in the XRPD analysis, which in turn led to an amount of recrystallized SAC being found in the sample after the 4-week period (All data for Rietveld fittings displayed in Supporting Information Figures S8 and S9).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical instability witnessed with IND/SAC/PEG 6000 cocrystals may be due to the PEG 6000 being soluble with one of the bulk components. Phaechamud et al noted solubilization of IND when using a 7:3 PEG 4000/PEG 400 mixture as an inert drug carrier, and El-Badry and colleagues found that pure PEG 4000 also had a solubilizing effect when interacting with IND. , Given these findings, it is reasonable for one to assume that when left for a period of time, the IND began to solubilize within the PEG 6000 matrix causing the chemical instability noted in the XRPD analysis, which in turn led to an amount of recrystallized SAC being found in the sample after the 4-week period (All data for Rietveld fittings displayed in Supporting Information Figures S8 and S9).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Phaechamud et al noted solubilization of IND when using a 7:3 PEG 4000/PEG 400 mixture as an inert drug carrier, and El-Badry and colleagues found that pure PEG 4000 also had a solubilizing effect when interacting with IND. 44,45 Given these findings, it is reasonable for one to assume that when left for a period of time, the IND began to solubilize within the PEG 6000 matrix causing the chemical instability noted in the XRPD analysis, which in turn led to an amount of recrystallized SAC being found in the sample after the 4-week period (All data for Rietveld fittings displayed in Supporting Information Figures S8 and S9). 5 and 6) show the bulk IND to be in the form of long irregularly shaped crystals, while the extruded IND/SAC cocrystals are shown to be equant shaped and in the form of agglomerates.…”
Section: Crystal Growth and Designmentioning
confidence: 99%
“…Then, tablets were weighed and kept for drying in an oven at 50 ℃ for 24 h. The weight of dried tablets was also recorded. Since part of tablets can dissolve during the dissolution test, water uptake% was calculated using the following equation: Water uptake% = (W1 − W2)/W2 × 100 where W1 is the weight of tablets at the end of the dissolution test and W2 is the weight of dried tablets [ 17 ]. Calculations were done in triplicate for more accuracy.…”
Section: Methodsmentioning
confidence: 99%